The enhancement of iron fuel cell on bio-cathode denitrification and its mechanism as well as the microbial community analysis of bio-cathode. (February 2019) - Li, Zehua; Zhang, Qinghua; Jiang, Qinrui; Zhan, Guoqiang; Li, Daping
Graphical abstract: Highlights: The iron fuel cell using inorganic electrons donor was designed for denitrification. The permeation of sodium acetate on the proton exchange membrane was confirmed. Iron fuel cell performed enhancement for denitrification at low C/N ratios. The mechanism of the enhancement of iron fuel cell was revealed. Abstract: To address the issue of insufficient electrons during denitrification, an iron fuel cell (IFC) bioreactor using iron as abiotic anode was designed. The nitrogen removal efficiency (NRE) of IFC (2.54 ± 0.016%) was significantly lower than microbial fuel cell (MFC) (32.58 ± 0.033%) with same bio-cathode under autotrophic conditions, which was due to the permeation of acetate on proton exchange membrane (PEM) affected the process of enriching autotrophic denitrifying bacteria by MFC. When used in heterotrophic conditions, the NRE of the closed-circuits of IFC was 29.04%, 10.53%, 8.33% higher than open-circuits, respectively, when the COD/nitrogen (C/N) ratios was 1, 2 and 3. The enhancement of IFC was the iron anode could convert a portion of nitrate to nitrite according to the abiotic cathode control experiments. The mainly functional bacteria of bio-cathode was Paracoccus (53.04%). In conclusion, the IFC could be a theoretical model for using inorganic electron donor during denitrification.